Co-producing knowledge about the Pacific walrus and climate change - Vera Metcalf; Daniel Apassingok; Iver Campbell; Arnold Gologergen; Bivers Gologergen; Edwin Noongwook; Henry P. Huntington; Joel L. Garlich-Miller; Devin L. Johnson (Arctic Science)
Pacific walruses (Odobenus rosmarus divergens, Illiger 1815) have long been vital to Indigenous communities along Alaska’s west coast. Although current harvest rates are sustainable, climate change and increased industrial activity in the range of this species pose threats to the population and to hunting safety and success. To gather information relevant to addressing these concerns, the Eskimo Walrus Commission and the US Fish and Wildlife Service held a workshop in August 2023 in Nome, Alaska, with experienced Yupik walrus hunters from the communities of Gambell and Savoonga on St. Lawrence Island, Alaska, and Federal walrus biologists. The 3-day event documented extensive information about walrus biology and behavior, which was used to improve a walrus population model. Workshop discussions also addressed concepts of sustainability and the future of walrus hunting. The workshop benefitted from prior collaboration between the biologists and some of the hunters on a walrus research cruise in the Chukchi Sea earlier the same summer, creating a foundation of common experience and interpersonal relationships. In the longer term, the workshop helped demonstrate the value of equitable collaboration towards shared goals, in part by allowing for open conversations rather than, for example, an extended question-and-answer session regarding model parameters.